Dental Biotribology - Zhou, Zhong-Rong. (Springer New York : Imprint: Springer, 2013)
Dental Biotribology summarizes the latest achievements in dental wear and is designed to help the reader better understand the relationship between structures and tribological properties of human teeth. This book provides guidance on the biomimic design of anti-wear engineering systems based on human teeth and also explains mechanisms of occlusal wear and erosion as well as fretting wear related to dental implants and orthodontics. Additionally, this book provides valuable insights into the development of improved dental materials and oral treatments. This book also: Explains the relationship between structures and tribological properties of human teeth Provides guidance on the biomimic design of anti-wear engineering systems based on human teeth Explains mechanisms of occlusal wear and erosion as well as fretting wear related to dental implants and orthodontics Provides valuable insights into the development of improved dental materials and oral treatments Dental Biotribology is an ideal book for researchers interested in tribology and oral rehabilitation.